Evaluatio of Outpatient Icd-10 Code Variations in the Mtbs Room of the Cinagara Health Center - Bhakti Ramadhan Mileniawan; Sali Setiatin; Heri Rukmana (International Journal of Psychology and Health Science, 2025)
This study aims to evaluate the variation in the use of International Classification of Diseases 10 (ICD-10) codes in the diagnosis recording of outpatient patients in the Integrated Management of Childhood Illness (IMCI) room of the Cinagara Public Health Center. This research employed a descriptive quantitative method with a cross-sectional approach. Data collection was carried out through observation of outpatient medical records from January to December 2024. The study sample included all medical records that met the inclusion criteria. The results showed variations in the use of ICD-10 codes, with a coding accuracy rate of 78.5%. The highest variations were found in the diagnosis of acute respiratory infections (ARI) and diarrhea. Further analysis indicated that these discrepancies could affect the accuracy of morbidity and mortality data, as well as the planning and evaluation of health programs. Factors influencing coding variations include the lack of health workers' understanding of ICD-10, workload, and the availability of appropriate coding guidelines. This study recommends periodic training on ICD-10 coding, the provision of comprehensive coding guidelines, and a routine audit system to improve the quality of diagnosis coding in the MTBS room of the Cinagara Public Health Center. These efforts are expected to improve the quality of health data and facilitate more appropriate decision-making. This research provides an important contribution to efforts to improve the quality of medical record data and health information systems at the Public Health Center level. By understanding the root of the problem and implementing the recommendations provided, it is hoped that the Cinagara Public Health Center can improve efficiency and effectiveness in health services.